Analysis of Sustainable Economic Growth through Strengthening Digitalprenuer Community MSME Actors - Tivana Putri Sahira; Ocdy Amelia; Halimatun Sa’diah; Dani Anggiyani; Oksi Kartini (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
Sustainable economic growth is one of the national development goals in Indonesia. Micro, Small, and Medium Enterprises (UMKM) play a crucial role in promoting sustainable economic growth; however, UMKM need to adapt to the developments in digital technology to compete and thrive in the market. The digitalpreneur community consists of UMKM practitioners who leverage digital technology to expand their businesses. This community can provide various benefits to its members, such as access to information and knowledge, business networks, and support for business development. This research employs a qualitative method with a case study approach. Data is gathered through in-depth interviews with informants. Based on the research findings, it is observed that the digitalpreneur community can contribute to sustainable economic growth in several ways, namely: 1) Enhancing the capacity and competitiveness of UMKM. 2) Improving market access. 3) Facilitating collaboration among UMKM.